Proceedings of the 12th International Conference on Natural Language Generation 2019
DOI: 10.18653/v1/w19-8665
|View full text |Cite
|
Sign up to set email alerts
|

Generating Abstractive Summaries with Finetuned Language Models

Abstract: Neural abstractive document summarization is commonly approached by models that exhibit a mostly extractive behavior. This behavior is facilitated by a copy-attention which allows models to copy words from a source document. While models in the mostly extractive news summarization domain benefit from this inductive bias, they commonly fail to paraphrase or compress information from the source document. Recent advances in transferlearning from large pretrained language models give rise to alternative approaches… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Recent advances in neural text generation have led to significant improvement in the quality of abstractive summarization (Radford et al, 2019;Gehrmann et al, 2019;Lewis et al, 2019). Despite this progress, there are still many limitations facing neural text summarization (Kryscinski et al, 2019), the most serious of which is the tendency to generate summaries that are not factually consistent with the input document; a factually consistent summary only contains statements that can be inferred from the source document.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances in neural text generation have led to significant improvement in the quality of abstractive summarization (Radford et al, 2019;Gehrmann et al, 2019;Lewis et al, 2019). Despite this progress, there are still many limitations facing neural text summarization (Kryscinski et al, 2019), the most serious of which is the tendency to generate summaries that are not factually consistent with the input document; a factually consistent summary only contains statements that can be inferred from the source document.…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the Reddit TIFU dataset suggested their own multi-level memory networks [43] that performed better than basic seq2seq and extractive models available by 2019. Within the 2019 TL;DR challenge, authors [44] compared LSTM, LSTM + copy, Transformer, Transformer + copy, and Transformer + pretrained models for n-gram abstractiveness in summarizations. The results have shown that the pretrained Transformer model unnecessarily outperformed the ground truth for news summarizations, but worked best for the Reddit data.…”
Section: Previous Applications Of Deep-learning Summarization Models ...mentioning
confidence: 99%
“…To analyze the abstraction level of TLDRHQ dataset, we plot the percentage of novel n-grams within the TLDR summary (See et al, 2017) in Figure 5 (b), as well as the TLDR's n-gram abstractiveness (Gehrmann et al, 2019) in Figure 5 (c) over the all instances in TLDRHQ dataset. As indicated, there are quite a large proportion of novel n-gram words appeared in the TLDR summary as the heat extent is mostly concentrated in the upper half of the y-axis.…”
Section: Dataset Analysismentioning
confidence: 99%